EFFECT OF MANIPURA CHAKRA YOGA ON VATIKA GRAHNI (IBS) PATIENTS (AYUSHDHARA, 2015)
Objective: Yoga and Tantra are found moving hand in hand with Ayurveda. Yoga procedure performed on abdominal vicinity effects through a basic anatomical entity Manipura Chakra. Manipura Chakra can be correlated with coeliac plexus and surrounding small plexuses. This concludes that all the abdominal organs are governed and regulated by Manipura chakra. The Yoga technique like Uddiyana Bandha, Bhastrika Pranayama, Pawanmuktasana etc affect directly on Manipura Chakra thereby affecting abdominal organ’s physiology and pathology like IBS and produce physical effect as increasing the Agni as well as psychological effects. The present study dignifies the hypothesis by clinical study.Method: For clinical study total 50 cases were registered were randomly selected diagnosed cases of Vatika Grahani (irritable bowel syndrome) group again divided into two subgroups 1) control and 2) intervention group consisting 25 in each. The intervention group are advised to do practice of Pavanamuktasana, Bhastrika Pranayama and Uddiyana Bandha for two months. The observations were analyzed using SPSS software 16.0 and results obtained.Result: In this study Vatika Grahani (IBS) - intervention sub group shows all the symptoms both pathological and psychological shown improvement which is statistically significant (p